Diet and diet‐related disorders in captive ruminants at the national zoological gardens of South Africa. Issue 5 (24th July 2014) - Gattiker, Cristina; Espie, Ian; Kotze, Antoinette; Lane, Emily P.; Codron, Daryl; Clauss, Marcus
<x xml:space="preserve">Abstract</x> Although diet‐related disorders have received much attention in the zoo literature, evidence‐based results on relationships between diet and disease are still rare, often due to a lack of quantitative dietary information that can be linked to clinical or necropsy reports. We investigated 24 species of captive ruminants from one facility for which quantitative feeding instructions and necropsy reports between 1991 and 2012 were available. Species were classified as grazer (GR), intermediate feeder (IM), or browser (BR). Feeding type and body mass were significantly correlated to the diet fed, with smaller and BR species receiving higher proportions of non‐roughage diet items. There were no significant differences between feeding types in the occurrence of parakeratosis/ruminitis/acidosis (PRA) at necropsy, but in body condition score, with BR more often in poor and less often in excellent body condition at necropsy. While there was no direct correlation between the proportion of non‐roughage diet items and PRA across species, there was a significant effect of the proportion of non‐roughage diet items on PRA when body mass was also taken into account: larger species, and those that received more non‐roughage diet items, had higher prevalence of PRA. The results underline that diet and lack of structured feed items can be associated with the disease complex of acidosis in ruminants, but also suggest that this is modified by factors related to animal size. These latter may include susceptibility to acidosis, or husbandry‐related opportunities to monopolize non‐roughage feeds and ingest higher proportions than intended by feeding instructions. Zoo Biol. 33:426–432, 2014. © 2014 Wiley Periodicals Inc.